THE ELEMENTS OF LANGUAGE CURRICULUM A Systematic Approach to Program Development - Brown, James Dean (Heinle & Heinle Publishers, 1995)
This text provides a practical, comprehensive overview of the different phases and activities involved in developing and implementing a sound, rational, and effective language program. It systematically describes and exemplifies all the elements of language curriculum design. Activities and exercises, graphic organizers, and sample language programs illustrate and promote pedagogically sound practice and effective integration of material.